ATIVIDADES DE NATUREZA GRUPAL NO CAMPO DA SAÚDE MENTAL E GERONTOLOGIA - Stumm, Eniva M. F.; Hildebrant, Leila M.; Santos, Cátia G. d.; Abreu, Paola B. d.; Spengler, Rúbia O. (Salão do Conhecimento, 2013)
Resumo